City 103 - Weibull, Lennart (University of Gothenburg, 1992)
This survey deals with radio listening, with special emphasis given to local broadcastings, and especially the local radio channel City 103. This channel is owned by the Swedish Employers' Confederation and started in autumn 1988. Its major content is modern hit list music together with news, local information and slogans from the Swedish Employers' Confederation. Questions were also asked about newspaper reading, leisure-time activities and opinions on radio.

This survey deals with radio listening, with special emphasis given to local broadcastings, and especially the local radio channel City 103. This channel is owned by the Swedish Employers´ Confederation and started in autumn 1988. Its major content is modern hit list music together with news, local information and slogans from the Swedish Employers´ Confederation. Questions were also asked about newspaper reading, leisure-time activities and opinions on radio.
City 103
Keywords: LEISURE TIME; FRITID; NEWSPAPER READERSHIP; TIDNINGS LÄSEKRETS; RADIO; RADIO; RADIO STATIONS; RADIOSTATIONER; RADIO LISTENING; RADIOLYSSNANDE; Media; Media; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap